Let's break down each part of Jeremiah's questions regarding his polynomial research.
Part A
Question 1: What are the different types of terms that appear in the polynomial expression?
In the expression \( P: 3(x^2 - x) + 4x - 1 - 5x \), the types of terms are:
- Constant term: \(-1\)
- Linear terms: \(4x\) and \(-5x\)
- Quadratic term: \(3x^2\)
Question 2: Use the Distributive Property to rewrite and simplify the expression.
To apply the Distributive Property: \[ P = 3(x^2 - x) + 4x - 1 - 5x \] First, distribute \(3\): \[ P = 3x^2 - 3x + 4x - 1 - 5x \] Now combine like terms: \[ P = 3x^2 + (-3x + 4x - 5x) - 1 = 3x^2 - 4x - 1 \]
Question 3: Use the Commutative Property to rewrite the expression in a different order.
Using the Commutative Property, we can rearrange the terms in any order: \[ P = -1 + 3x^2 - 4x \] or \[ P = 3x^2 - 1 - 4x \]
Question 4: Jeremiah rewrites the expression as \( 3x^2 - (4x + 1) \). Explain clearly why this statement is or is not equivalent to the original expression.
The expression \( 3x^2 - (4x + 1) \) is equivalent to the original expression \( 3x^2 - 4x - 1 \) because:
- When you distribute the negative sign in \( -(4x + 1) \), you get \(-4x - 1\).
- Therefore, combining gives: \[ 3x^2 - 4x - 1 \] Which is indeed the same as the simplified form of \( P \).
Part B
Question 5: Write an expression \( Q \) that is similar to \( P \) but with different coefficients.
An example of such an expression could be: \[ Q: 2(x^2 - 2x) + 5x + 3 - 4x \]
Question 6: Find the sum of the expressions \( P + Q \).
First, we simplify \( Q \): \[ Q = 2(x^2 - 2x) + 5x + 3 - 4x = 2x^2 - 4x + 5x + 3 - 4x = 2x^2 + 3 - 3x \]
Now, we compute \( P + Q \): \[ P + Q = (3x^2 - 4x - 1) + (2x^2 - 3x + 3) \] Combine like terms: \[ (3x^2 + 2x^2) + (-4x - 3x) + (-1 + 3) = 5x^2 - 7x + 2 \]
Question 7: Find the difference between the expressions \( P - Q \).
Calculating \( P - Q \): \[ P - Q = (3x^2 - 4x - 1) - (2x^2 - 3x + 3) \] Simplifying: \[ 3x^2 - 4x - 1 - 2x^2 + 3x - 3 = (3x^2 - 2x^2) + (-4x + 3x) + (-1 - 3) = x^2 - x - 4 \]
Question 8: Are the expressions \( P + Q \) and \( P - Q \) closed under addition and subtraction, respectively?
Yes, both expressions \( P + Q \) and \( P - Q \) are closed under addition and subtraction, respectively, because the sum and difference of polynomials are still polynomials.
Part C
Question 9: Are the two expressions shown equivalent to each other?
To check \( - (P + Q) = P - Q \): Using a previous result from Questions 6 and 7:
- \( P + Q = 5x^2 - 7x + 2 \)
- Therefore, \( - (P + Q) = - (5x^2 - 7x + 2) = -5x^2 + 7x - 2 \)
Now \( P - Q = x^2 - x - 4 \):
- The two expressions are not equivalent, since: \[
- (P + Q) \neq P - Q \]
Properties used:
- The distributive property to multiply \( -1 \) across \( P + Q \).
Part D
Question 10: What is the simplified form of the polynomial division \( \frac{35}{5x} \)?
Simplifying gives: \[ \frac{35}{5} \cdot \frac{1}{x} = 7 \cdot \frac{1}{x} = \frac{7}{x} \]
Question 11: What is the result of dividing the revenue function \( R(x) = 8x^4 - 20x^3 + 40x^2 \) by \( 2x^2 \)?
Perform the division: \[ \frac{8x^4}{2x^2} - \frac{20x^3}{2x^2} + \frac{40x^2}{2x^2} = 4x^2 - 10x + 20 \]
Part E
Question 12: What is the product of \( X \cdot Y \)?
\[ X = 2x - 1, \quad Y = 3x + 5 \] Using the distributive property (FOIL method): \[ X \cdot Y = (2x - 1)(3x + 5) = (2x)(3x) + (2x)(5) - (1)(3x) - (1)(5) = 6x^2 + 10x - 3x - 5 \] Combining like terms: \[ = 6x^2 + 7x - 5 \]
Question 13: Before you calculated the result, could you have known that the resulting expression is a polynomial?
Yes, the product of two linear polynomials always results in a polynomial, specifically a polynomial of degree equal to the sum of the degrees of the factors. Here, both \( X \) and \( Y \) are linear (degree 1), so their product is a quadratic polynomial (degree 2), confirming the result is a polynomial.